2007
DOI: 10.1073/pnas.0610132104
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence that Whorfian effects are stronger in the right visual field than the left

Abstract: The Whorf hypothesis holds that differences between languages induce differences in perception and/or cognition in their speakers. Much of the experimental work pursuing this idea has focused on the domain of color and has centered on the issue of whether linguistically coded color categories influence color discrimination. A new perspective has been cast on the debate by recent results that suggest that language influences color discrimination strongly in the right visual field but not in the left visual fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

21
141
4
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(172 citation statements)
references
References 18 publications
21
141
4
3
Order By: Relevance
“…In contrast, there was no such difference in the LVF, although both within-category and between-category deviants provoked reliable vMMN effects compared with the standard stimuli. This result converges with previous behavioral and functional MRI data of the lateralized Whorfian effect (14,15,17,24). Color patches of an unexpected hue exposed briefly in the RVF only, and hence received initially in the left, language-dominant cerebral hemisphere, elicit less of a surprise response in the brain when they belong to the same lexical category as an expected color than do colors perceptually equidistant from the expected color but belonging to a different lexical category.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, there was no such difference in the LVF, although both within-category and between-category deviants provoked reliable vMMN effects compared with the standard stimuli. This result converges with previous behavioral and functional MRI data of the lateralized Whorfian effect (14,15,17,24). Color patches of an unexpected hue exposed briefly in the RVF only, and hence received initially in the left, language-dominant cerebral hemisphere, elicit less of a surprise response in the brain when they belong to the same lexical category as an expected color than do colors perceptually equidistant from the expected color but belonging to a different lexical category.…”
Section: Resultssupporting
confidence: 92%
“…Previous research on early ERP evidence of categorical color perception has shown that it varies predictably according to language-specific terminology (25,26) and that it very probably is automatic and preattentive (28). The present study has shown that the categorical modulation of the vMMN by color difference is lateralized to the RVF and so presumably is controlled by the left cerebral hemisphere, where most language functions are housed and where this finding confirms much behavioral (2,(14)(15)(16)(17)19) and neurophysiological (23)(24)(25)(26)28) evidence. Lateralized Whorfian effects on early color processing strongly appear to be automatic and preattentive.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The target detection task is appropriate as the task has been used to demonstrate CP in both infants and adults (10) and investigate hemispheric asymmetries in adult color CP with a reaction time measure (16). The original version of the target detection task explored color CP in infants and adults by using an eyemovement measure.…”
mentioning
confidence: 99%
“…The conventional method is to present stimuli for Ϸ150-250 ms and measure reaction time to these lateralized stimulus presentations (14,16). Rapid stimulus presentation to one visual field ensures that direct projections of the stimulus are confined to the contralateral hemisphere.…”
mentioning
confidence: 99%